As crises do jornalismo no contexto digital brasileiro : um estudo sobre produção e imaginário - Vasconcellos, Fernanda Cristine (2021)
This research investigates the crisis of journalism in the digital and postmodern context, with special emphasis on the Brazilian industry. It aims to answer the question: “What is the crisis of journalism?”. The comprehensive sociology (MAFFESOLI, 2010; SILVA, 2012a; 2017), which is the epistemological basis of this work, offers a three-step guide for this study, built upon the concepts of Strangeness, Penetration, and Unraveling (SILVA, 2019). The bibliographical and documentary research (GIL, 2008; STUMPF, 2008) of this investigation was developed with a description of journalism and its role and an analysis of the profound social and technological transformations we live nowadays. We have studied and updated—as well as investigated the Brazilian particularities—of the journalism crisis as described by Todd Gitlin (2011): financing, circulation, attention, authority, and deference. Supported by other researches and authors, we have found other four crises, namely presence, work, representation, and disinformation. These nine crises are the starting point for two field researches. In the first, an Ethnography and Participant Observation (ANGROSINO, 2009) took place inside O Globo newsroom to understand the consequences of these crises in the daily routine of journalism; in the second, Comprehensive Interviews (KAUFMANN, 2013) were made with ten influential members from different areas of society to draw an imaginary of Brazilian journalism. In both cases, the data was analyzed through the Discursive Analysis of the Imaginary (SILVA, 2019). As a result, this work presents some inferences, such as all the crises of journalism are linked to a deeper crisis in the relationship of journalism, journalists, and newspapers with its audiences; the journalism crises results in commercial interferences; the purely quantitative search and analysis of audience data produces a mass -oriented view of the reader, which creates a gap between audiences and journalism; the clickbait techniques are perceived by part of the audience, thus making fake news look real and real news look fake; the crisis of authority and trust is the biggest challenge that journalism faces today; the audiences avoid the news because they perceive it as too negative. Finally, we suggest some ways by which journalism is able to build a relationship with its audiences, thus overcoming the crises that it faces.